Intercultural communication barriers in South Korea: The case of Indonesian international students - Beni Wijaya; Putri Sanawiyah; Zakaria Zakaria; Darmaliana Darmaliana; Leni Rohliah; Sintia Pertiwi (Universitas Merdeka Malang, 2025)
This study aimed to identify the barriers to intercultural communication that Indonesian international students encounter in South Korea and to propose a solution. A qualitative descriptive methodology, utilizing in-depth interviews for data gathering, was employed. The study involved interviews with 27 IISMA recipients to gain insights into their experiences with intercultural communication. The results showed that participants struggled to communicate effectively with people from other cultures while studying in South Korea. These problems included anxiety, the assumption that people were more alike than different, ethnocentrism, assumptions, biases, language difficulties, and difficulties with nonverbal communication. This study identified methods to overcome intercultural communication obstacles, enabling international students to develop self-awareness and deepen their cultural understanding, thereby fostering positive relationships with peers, learning the Korean language, utilizing translation applications, being kind and leaving a positive impression on the South Korean local community.